Shell Anomalies in the Elongated Tortoise Indotestudo elongata (Blyth, 1853) at Ban Kok Village, Amphur Muncha Kriri, Khon Kaen Province - ศรีประทีป, กัลยา; พรหมกุล, วรัญญู (KKU Science Journal, 2015)
Exploration of shell anomalies in the elongated tortoise Indotestudo elongata is studied at Ban Kok Village, Amphur Muncha Kriri, Khon Kaen Province, from October 2013 to January 2014. A total of 514 tortoises were corrected and determined the shell anomalies. Forty-one tortoises had shell anomalies that could be separated into 3 groups. The first group, 24 tortoises (4.67%) had the additions or reductions in the number of scutes especially vertebral and costal scutes. The second group, 12 tortoises (2.33%) had the lesion or fracture of shell and the third group, 5 tortoises (0.97%) had deformation. Anomalies were found only in the carapace. The lesion or fractures on the carapaces were caused by accident due to living with communities in the village. This study is the information for the way to protect and conserve elongated tortoise with the communities.